Durable control of locally recurrent renal cell carcinoma using stereotactic body radiotherapy - Maclean, Jillian (BMJ Publishing Group, 2014)
Renal cell carcinoma (RCC) is generally poorly responsive to conventional radiation doses, and patients with inoperable local recurrence have limited therapeutic options. Stereotactic body radiotherapy (SBRT) is an increasingly available technology that allows delivery of a radiation schedule providing doses far more biologically effective against cancer cells than conventional radiotherapy. We present a case where durable disease control was achieved using SBRT in a patient with inoperable locally recurrent RCC who presented 18 years from original nephrectomy. The patient remains asymptomatic with no evidence of active disease 30 months following SBRT. This case highlights the need to reconsider the role of therapies with continuing advances in technology.